Indung meets Sayang dancers : issues of putting folk genres on stage. - Chan, Cheong Jan (LAP Lambert Academic Publishing, 2012)
In 21 July 2011, after a gap of more than ten years, Indung was staged again in Kuala Lumpur under the 82 years old Hamiah Haji Ahmad at a cross cultural dance festival organized by the National Department for Culture and Arts. This time, Indung, performed by elder villagers, was placed between tap dance performances by the Sayang Dancers which consisted of young female dancers. Finally, the observation of this performance presents strong evidence of clash of aesthetic expectations and ritual requirements from the performers and the audience. A framework or model to effectively representing the work-dependent folk genre to the public is urgently needed to prevent further attempt to stage Indung without considering the unfulfilling sentiments of the villagers and the audience.